EMPOWERING SMES TOWARD GLOBAL COMPETITIVENESS THROUGH DIGITALIZATION OF BUSINESS OPERATIONS AND INTEGRATED FINANCIAL SYSTEM MODERNIZATION - Sofyan Halim; Muhammad Laras Widyanto; Rujito Rujito (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in Indonesia’s national economy, contributing 61% of GDP and absorbing 97% of the national workforce. Despite this significance, MSMEs face persistent structural challenges including manual production processes, inadequate packaging technology, limited digital marketing capabilities, and the absence of integrated financial recording systems. This community service (PkM) activity was conducted by the Faculty of Economics and Business, Universitas Mercu Buana, in partnership with the MSME Community of Pondok Melati, Bekasi City, involving 30 active MSME practitioners. The program applied a Community-Based Empowerment and Technology Integration approach through five systematic stages: needs assessment, capacity building training, technology implementation, intensive mentoring, and sustainability evaluation. Key interventions included vacuum and nitrogen packaging technology, Point of Sales (POS) systems, the Keuangan Bisnisku digital accounting application, digital marketing training via social media platforms, and the formation of Digital Champions. Evaluation results using a Likert-scale (1–4) questionnaire revealed mean scores of 3.20–3.80 across all indicators, categorized as High to Very High. The program effectively enhanced participants’ business management capacity, improved financial reporting accuracy by up to 92%, and strengthened digital marketing skills. The program contributes to SDG 5, 8, 9, and 17, and supports the Asta Cita national priority agenda.